2009
DOI: 10.1016/j.foodcont.2008.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of chemical dip and/or carrageenan coating and/or controlled atmosphere on quality of fresh-cut banana

Abstract: a b s t r a c tThe combined effect of chemical dip and/or edible coating and/or controlled atmosphere (CA) on quality of fresh-cut banana was investigated. Banana slices were subject to a 3-min dip into a solution containing 1% (w/v) calcium chloride, 0.75% (w/v) ascorbic acid and 0.75% (w/v) cysteine and/or combined with a carrageenan coating and/or combined with controlled atmosphere (3% O 2 + 10% CO 2 ). Physico-chemical and microbiological qualities were evaluated during 5 days of storage at 5°C. Dip combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
147
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(167 citation statements)
references
References 30 publications
12
147
0
8
Order By: Relevance
“…The author describes that the content of soluble solids in the control sample and samples treated with alginate showed significant differences (p ≤ 0.05) during storage. Bico et al (2009) observed an increase in soluble solids content of fresh-cut bananas stored at 5 °C for 5 days treated with coating of carrageenan and a preservative solution under controlled atmosphere.…”
Section: Characterization Of Pearsmentioning
confidence: 88%
See 1 more Smart Citation
“…The author describes that the content of soluble solids in the control sample and samples treated with alginate showed significant differences (p ≤ 0.05) during storage. Bico et al (2009) observed an increase in soluble solids content of fresh-cut bananas stored at 5 °C for 5 days treated with coating of carrageenan and a preservative solution under controlled atmosphere.…”
Section: Characterization Of Pearsmentioning
confidence: 88%
“…Fontes et al (2008) used an edible coating of alginate on minimally processed apples stored at 2 °C for 13 days and found that the pH of the fruits remained unchanged during storage. Bico et al (2009) Same capital letters in the same line and same lowercase letters in the same columns indicate that the samples did not differ significantly (p ≥ 0.05). the metabolic activities of the fruit reducing the degradation of polysaccharides and changes in the soluble solids content.…”
Section: Characterization Of Pearsmentioning
confidence: 98%
“…The overall least significance difference (LSD; p ≤ 0.05) was calculated and used it to detect significant differences among all the treatments and control set. Relationships among measurement variables were studied by using the correlation coefficient (Bico et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The use of hydrogen peroxide is recommended for treatment of vegetables thanks to its low toxicity and safe decomposition of O2 and H2O. However, microbial safety is one of the most important factors to be considered for the preservation of minimally processed foods (Bico et al, 2009). E.coli in fresh carrots was not detected.…”
Section: Resultsmentioning
confidence: 99%